The Analysis idiom in Nadin Amizah’s “Bertaut” song lyrics. - Jasmine, Shoofy; Gorat, Lenny Marsella; Andreas, Andreas; Purba, Ina; Nasution, Muhammad Shofi; Putri, Dian Marisha (Universitas Harapan Medan, 2023)
This article presents and idiomatic analysis of the lyrics of Nadin Amizah, a talented Indonesian singer. The data collected was analyzed using qualitative methods, The data in this study were taken directly from Nadin Amizah's